The role of frugivorous birds in fruit removal and seed germination of the invasive alien Cotoneaster franchetii in central Argentina. (13th March 2018) - Díaz Vélez, María C.; Sérsic, Alicia N.; Traveset, Anna; Paiaro, Valeria
Abstract: Many invasive plant species have fleshy fruits that are eaten by native frugivorous birds which disperse their seeds and may facilitate their germination, playing an important role in plant invasion success. The fleshy‐fruited shrub Cotoneaster franchetii (Rosaceae) is an important invasive alien in the mountainous regions of central Argentina. To determine the role of avian frugivorous in fruit removal of this species, we conducted a frugivore exclusion experiment including bagged and unbagged branches in 75 plants of C. franchetii . At the end of the dispersal period, we compared the percentage of missing fruits (removed by birds + naturally dropped) in unbagged branches with the percentage of naturally dropped fruits in bagged branches. To assess whether any mechanism acting on seeds during their passage through bird guts (de‐inhibition by pulp removal and/or seed scarification) affects seed germination of this species, we compared percentage and speed of germination among seeds obtained from faeces of the native frugivorous Turdus chiguanco, from manually de‐pulped fruits, and from intact fruits. The percentage of missing fruits per shrub in unbagged branches was significantly higher than the percentage of naturally dropped fruits in bagged branches, suggesting that frugivorous birds play an important role in fruit removal of C. franchetii in the study area. Seeds from bird faeces and from manually de‐pulped fruits germinated in higher percentage and faster than seeds from intact fruits. Germination percentage and speed of seeds from manually de‐pulped fruits were significantly higher than those of gut‐passed seeds. These results indicate that T. chiguanco increases and accelerates seed germination of C. franchetii through pulp removal, but not through seed scarification. Overall, our findings indicate that native frugivorous birds facilitate the dispersal and germination success of C. franchetii, likely playing an important role in its invasion throughout the mountainous region of central Argentina.